2013
DOI: 10.1093/jmcb/mjs053
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 kinase activity depends on cis-autophosphorylation of its activation loop

Abstract: The multitude of mechanisms regulating the activity of protein kinases includes phosphorylation of amino acids contained in the activation loop. Here we show that the serine/threonine kinase HIPK2 (homeodomain-interacting protein kinase 2) is heavily modified by autophosphorylation, which occurs by cis-autophosphorylation at the activation loop and by trans-autophosphorylation at other phosphorylation sites. Cis-autophosphorylation of HIPK2 at Y354 and S357 in the activation loop is essential for its kinase fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 56 publications
8
90
2
Order By: Relevance
“…The capacity of tyrosine phosphorylation in DYRKs and related CMGC kinases such as GSK3 and HIPK2 is essential for the activation of these kinases and has been thought to be strictly limited to cis-autophosphorylation of one specific tyrosine residue in the activation loop [13,14,32]. Here we show that DYRK1A-Y321F and DYRK2-Y382F are capable of phosphorylating other tyrosines when expressed in E. coli (Fig.…”
Section: Tyrosine Kinase Activity Of Dyrks Is Not Limited To the Consmentioning
confidence: 60%
See 1 more Smart Citation
“…The capacity of tyrosine phosphorylation in DYRKs and related CMGC kinases such as GSK3 and HIPK2 is essential for the activation of these kinases and has been thought to be strictly limited to cis-autophosphorylation of one specific tyrosine residue in the activation loop [13,14,32]. Here we show that DYRK1A-Y321F and DYRK2-Y382F are capable of phosphorylating other tyrosines when expressed in E. coli (Fig.…”
Section: Tyrosine Kinase Activity Of Dyrks Is Not Limited To the Consmentioning
confidence: 60%
“…Phosphorylation of this tyrosine stabilizes the active conformation by allowing electrostatic interactions of the phosphate with two conserved arginine residues [7]. Only the members of the MAPK family are regulated by upstream kinases (MAP2K), whereas DYRKs, homeodomain-interacting protein kinase 2 (HIPK2), GSK3 and intestinal cell kinase autophosphorylate on the corresponding tyrosine [8][9][10][11]. On the other hand, CLKs lack the conserved tyrosine residue in the activation loop but are also capable of tyrosine autophosphorylation [4,6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tyr354 has been previously implicated in the regulation of HIPK2 kinase activity. 22,23 This motivated us to raise a phosphorylation-specific antibody against this pTyr354 of HIPK2. We first assessed the specificity of the pTyr354 antibody.…”
Section: Src Phosphorylates Hipk2 At Tyrosine Residuesmentioning
confidence: 99%
“…Of note, wild-type HIPK2 has recently been shown to be autophosphorylated in cis at Tyr354 using mass spectrometry. 22,23 To determine whether Src can mediate phosphorylation of Tyr354 in trans, we used kinase-dead HIPK2 K221A , which lacks autophosphorylating activity, as a substrate for Src and analyzed its phosphorylation at Tyr354 using our phospho-specific pTyr354 HIPK2 antibody. Indeed, immunoblotting revealed that expression of kinase-active Src mediates phosphorylation of HIPK2 K221A at Tyr354 (Fig.…”
Section: Src Phosphorylates Hipk2 At Tyrosine Residuesmentioning
confidence: 99%
See 1 more Smart Citation